2017
DOI: 10.1108/tqm-06-2016-0051
|View full text |Cite
|
Sign up to set email alerts
|

Improving health care quality: the implementation of whistleblowing

Abstract: Purpose – In line with the current literature, the purpose of this paper is to contribute to a better understanding of whistleblowing procedures and their influence on overall organisational quality. To this end, institutional, organisational, and cultural barriers to whistleblowing implementation have been investigated.\ud Design/methodology/approach – A qualitative analysis based on three explorative case studies investigates and compares different whistleblowing practices implemented in health care organisa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 62 publications
0
27
0
Order By: Relevance
“…This strategic conduct might contribute to the improvement of the physical and psychological conditions not only of the patients directly involved in the service process, but also of the social context, not forgetting to foster public awareness about how healthcare advancement benefits social wellness [99,100]. Even if a service ecosystem approach to innovation offers interesting insights for marketing and management to rethink, redesign, rebuild and maintain the practices at the core of value co-creation, much research is still needed to improve the potential of innovation on the reconfiguration of different service ecosystems.…”
Section: Implications and Further Researchmentioning
confidence: 99%
“…This strategic conduct might contribute to the improvement of the physical and psychological conditions not only of the patients directly involved in the service process, but also of the social context, not forgetting to foster public awareness about how healthcare advancement benefits social wellness [99,100]. Even if a service ecosystem approach to innovation offers interesting insights for marketing and management to rethink, redesign, rebuild and maintain the practices at the core of value co-creation, much research is still needed to improve the potential of innovation on the reconfiguration of different service ecosystems.…”
Section: Implications and Further Researchmentioning
confidence: 99%
“…Out of these, 11 studies included in the final review of this study originated from five countries: the USA (n = 3), the UK (n = 2), Australia (n = 2), Italy (n = 1), the Netherlands (n = 1), Finland (n = 1) and Wales (n = 1) respectively. Five of the included studies were qualitative in design (Ciasullo et al, 2017;Jackson et al, 2010aJackson et al, , 2010bAttree, 2007;Peters et al, 2011;Jones and Kelly, 2014) The included studies presented clear statements of their aims and most studies identified their research designs and were suitable to address the aims of the research. The aims were all aligned to the findings.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…Although what one nurse may perceive as intended wrongdoing another nurse may perceive as poor judgement or carelessness on the part of the wrongdoer. Ciasullo et al (2017) revealed that the apparent lack of managers and colleagues' support was also a significant stimulus that encouraged health-care professionals and administrative employees to remain silent. This raises the question as to why it seems to be less supported to raise concerns openly in a field of health care that should be promoting honesty and openness.…”
Section: Hesitancementioning
confidence: 99%
“…It can be referred to as extension of the employee involvement element in TQM implementation. Further, the work was extended by enhancing the interpretation of whistleblowing and its capacity to influence overall organizational quality [12] . The work highlighted the implementation of whistleblowing procedures by Italian National Health Services(INHS).…”
Section: Employee Involvement and Total Quality Managementmentioning
confidence: 99%